Teaching and learning second language pragmatics for intercultural understanding - McConachy, Troy, 1980-; Liddicoat, Anthony J. (New York, NY : Routledge, 2022)
"This collection argues for the need to promote intercultural understanding as a clear goal for teaching and learning pragmatics in second and foreign language education. The volume sees the learning of pragmatics as a challenging yet enriching process whereby the individual expands their capacity for understanding how meaning making processes influence social relationships and how assumptions about social relationships shape the interpretation and use of language in context. This locates pragmatics within a humanistically oriented conception of learning where success is defined relative to the enrichment of human understanding and appreciation of difference. The book argues that intercultural understanding is not an "add on" to language learning but central to the learner's ability to understand and construct meaning with individuals from diverse linguistic and cultural backgrounds. Chapters analyse teachers' and learners' ways of making sense of pragmatics, how their assumptions about social relationships impact their perceptions of language use, and how reflection on pragmatic judgments opens up possibilities for developing intercultural understanding. This book will be of interest to students and scholars in intercultural communication, language education, and applied linguistics"--
Introduction: Second language pragmatics for intercultural understanding / Troy Mcconachy and Anthony J. Liddicoat -- Negotiating politeness practices and interpersonal connections in L2 Japanese : insights from study abroad narratives / Troy McConachy and Hanako Fujino -- "But in England they're certainly very polite, so you mustn't forget that" : young EFL learners making sense of pragmatic practices / Milica Savić and Anders Myrset -- Exploring framing categories in language learners' intercultural positioning : "Asia" and "the West" / Barbara Pizziconi -- Literary pragmatics and intercultural dialogue in the beginning language class : a study in social reading / Peju Alfred and Chantelle Warner -- Mixed-culture discussion activities as a tool for developing pragmatic and intercultural awareness / Andrew Barke and Momoyo Shimazu -- Concept-Based Instruction for teaching and learning L2 (im)politeness / Natalia Morollón-Martí -- Co-constructing non-essentialist pedagogy : supporting teachers to support learners' translingual agency through L2 pragmatics instruction / Noriko Ishihara and Adriana Porcellato -- Intercultural competence and pragmatics in the L2 classroom : views of in-service EFL teachers in primary, secondary, and adult education / Gila A. Schauer -- Towards a new measurement of intercultural (communicative) competence : assessing the pragmatic competence of intercultural speakers / Ariadna Sánchez-Hernández and Carmen Maíz-Arévalo.
Off-Campus Access: User ID and Password Required
On-Campus Access: User ID or Password Required
Access type: Non-expiring Rental
Includes bibliographical references and index.
ENH
Mode of access: Internet
Keywords: Second language acquisition; Language and languages -- Study and teaching; Pragmatics; Intercultural communication; Multicultural education; Language and culture; English language; Electronic books